1979
DOI: 10.1063/1.90700
|View full text |Cite
|
Sign up to set email alerts
|

Chromium profiles in semi-insulating GaAs after annealing with a Si3N4 encapsulant

Abstract: Quantitative Cr profiles have been determined on semi-insulating GaAs by secondary-ion mass spectrometry (CAMECA IMS 300). It is shown that after thermal annealing (900 °C, 20 min) under Si3N4, Cr diffuses towards the GaAs surface, leaving a Cr concentration depletion zone underneath. This zone becomes conductive with a carrier concentration of n∼2×1016 cm−3. Some consequences of these findings are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

1980
1980
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(12 citation statements)
references
References 5 publications
1
10
0
1
Order By: Relevance
“…Surface oxides will enhance the yield of positive secondary ions within the first hundred angstroms (32,33). Surface oxides will enhance the yield of positive secondary ions within the first hundred angstroms (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Surface oxides will enhance the yield of positive secondary ions within the first hundred angstroms (32,33). Surface oxides will enhance the yield of positive secondary ions within the first hundred angstroms (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…As for the excess doping efficiency, a number of workers (12)(13)(14)(15)(16) reported that a conductive n-type surface layer is formed during the thermal anneal of …”
Section: ( 1 + -If#mentioning
confidence: 99%
“…[8] However, unlike undoped SIGaAs, GaAs : Cr is not stable under thermal annealing. [9,10] Thus, it is expected that GaAs : Cr would have a different behavior with HELI irradiation compared to that of SI-GaAs. In this work, we essentially address this issue -the difference in structural evolution of SI-GaAs and GaAs : Cr by HELI irradiation.…”
Section: Introductionmentioning
confidence: 99%